Supporting people with dementia to walkabout safely outdoors: development of a structured model of assessment. (27th March 2015) - Bantry White, Eleanor; Montgomery, Paul
Abstract: People with dementia while missing are at risk of harm including death. Yet, welfare concerns arise when freedom to walkabout outdoors is restricted and in particular, getting lost is a risk factor for admission to long‐term care. Accurate methods of assessing the risks posed to community‐dwelling people with dementia from getting lost are needed to ensure intervention is proportionate. Currently available assessment tools focus upon the identification of dementia‐related changes in a person's walking behaviour, traditionally referred to as 'wandering'. 'Wandering' and getting lost are conceptually distinct; measures of 'wandering' are not sufficient to support the assessment of risk while walking outdoors. The objective of this study was to develop an assessment schedule that can evaluate safety in community‐dwelling people with dementia who walkabout outdoors. A structured assessment schedule was generated from research on the aetiology of getting lost, a review of existing assessment tools, an observational study of incidents of getting lost and qualitative data from families experiencing this issue. A content validity study was then undertaken with a panel of 17 health and social care practitioners and researchers in the field. A schedule of 7 domains and 38 items was generated, 33 of which were deemed valid by the expert panel. Panel feedback suggests the schedule needs to be used flexibly to reflect an individual's unique living circumstances. Reflecting the complex aetiology of getting lost, considerable challenges exist when assessing risk in this field. The implications of this study for practitioners are discussed with reference to the merits of narrative and structured models of assessment, and the balance between objective safety and subjective well‐being that is required when making decisions about intervention. The direction of further research is examined as a means of supporting professional assessment of this complex issue.